Generation of KCL035 research grade human embryonic stem cell line carrying a mutation in HBB gene - Heema Hewitson; Victoria Wood; Neli Kadeva; Glenda Cornwell; Stefano Codognotto; Emma Stephenson; Dusko Ilic (Stem Cell Research, 2016)
The KCL035 human embryonic stem cell line was derived from an embryo donated for research that carried a mutation in the HBB gene, which is linked to the β-thalassemia syndrome. The ICM was isolated using laser microsurgery and plated on γ-irradiated human foreskin fibroblasts. Both the derivation and cell line propagation were performed in an animal product-free environment. Pluripotent state and differentiation potential were confirmed by in vitro assays.